Franz Overbeck: on the theory and practice of an antifundamentalist and antichristian humanism (2020)
Franz Overbeck, professor of theology at the University of Basel, friend of Friedrich Nietzsche has developed a very personal version of humanism, far beyond the illusions of traditional humanism orientated towards an ideal Antiquity. Overbeck’s humanism is a critical and sceptical one, far away from all humanist dogmatism. Overbeck defends Man against the impositions of Christian anthropology as well as against the impositions of the Niezschean belief in a overhuman future of mankind.